Antioxidant properties and cytotoxicity of successively macerated Christia vespertilionis (L.f) Bakh.f. root and leaf against breast cancer cell lines - Lee, Joanna Jinling (2020)
Breast cancer is the most diagnosed cancer among women worldwide with substantial after-treatment effects. Even with the constant improvement of current therapeutic strategies, the survival rate of breast cancers continues to decline over the decades. Breast cancer is slowly moving into the category of chronic disease due to various barrier limitations such as poor prognosis, non- specific treatment and silent metastasis. Furthermore, severe side effects from chemotherapy agents were seen to potentially harm healthy cells instead of targeting only cancerous cells. Christia vespertilionis, a tropical Southeast Asia Fabaceae, is a medicinal plant known for its anti-cancer and anti-inflammatory properties. The objective of this study was to determine the antioxidant activity and cytotoxicity of the root and leaf of C. vespertilionis against breast cancer cell lines. Both the roots and leaves of the plant were extracted using the successive solvent maceration method with hexane, chloroform, ethyl acetate and methanol. All the crude extracts were compared for the best bioactivity and was further fractionated by column chromatography method. Antioxidant activity of all the extracts and fractions were determined using TPC, DPPH and β-carotene bleaching assay. Cytotoxicity of all the extracts and fractions were determined using MTT assay. The potentially active compounds and phytochemical components of the active extract and fraction were tentatively assigned and identified using LC-MS/MS. Based on the results, the root extracts of C. vespertilionis showed better bioactivity compared to the leaf extracts. The ethyl acetate root extract showed the highest TPC (TPC = 192.12 ± 4.41 μg GAE/g) and antioxidant activity (DPPH IC50 = 70.16 ± 1.49 μg/mL and lipid peroxidation inhibition = 59.52 ± 0.57 %) compared to others (p < 0.05). The extract also exhibited highly selective cytotoxic effects in a dose-dependent manner against MDA-MB-231 and MCF-7 breast cancer cell lines but not toward the normal 3T3 cells. The IC50 of the treated MDA-MB-231, MCF-7 and 3T3 cells were 11.34 ± 1.20, 44.65 ± 5.78 and 77.38 ± 4.71 μg/mL, respectively. Amongst the ethyl acetate root fractions, CV E4 fraction exhibited the highest TPC and lipid peroxidation inhibition (330.92 ± 7.30 μg GAE/g and 83.68 ± 1.31 %, respectively). The highest free radical scavenging activity however was seen in CV E6 fraction. Meanwhile, CV E3 fraction exhibited both significant and selective cytotoxicity in a dose-dependent manner. The fraction’s IC50 was 5.72 ± 0.99, 8.98 ± 1.06 and 49.90 ± 8.63 μg/mL against MDA-MB-231, MCF-7 and 3T3 cell lines, respectively. Further qualitative phytochemical characterization using LC-MS/MS on the most active extract and fraction suggested the presence of flavonoids, terpenoids, coumarins and quinones that contributes to the antioxidant and cytotoxic properties. In conclusion, the study suggests C. vespertilionis as a potential medicinal plant that is selective toward breast cancers. The phytochemicals present in ethyl acetate root extract and CV E3 fraction demonstrated notable cytotoxicity especially toward MDA-MB-231 cell line.